Involvement of thyroid hormones in the alterations of T-cell immunity and tumor progression induced by chronic stress - Frick, Luciana Romina (2009)
Stress alters the neuroendocrine system, immunity, and cancer. Although the classic stress hormones are glucocorticoids and catecholamines, thyroid hormones have also been related to stress. We recently reported that chronic restraint stress impairs T-cell mediated immunity and enhances tumor growth in mice.